Howard Watkins Visits Chris' Grandmother Winifred Wehe Loehr - Watkins, Howard::::::::: (1983)
Howard Watkins wearing "Cogito Ergo Sum Cogito" T-shirt and Winifred Wehe Loehr 10457 Reynolds Way, Truckee